2023
DOI: 10.3390/ma16083111
|View full text |Cite
|
Sign up to set email alerts
|

Do the Mechanical Properties of Calcium-Silicate-Based Cements Influence the Stress Distribution of Different Retrograde Cavity Preparations?

Abstract: The aim of the present study was to investigate the influence of the mechanical properties of three different calcium-silicate-based cements on the stress distribution of three different retrograde cavity preparations. Biodentine™ “BD”, MTA Biorep “BR”, and Well-Root™ PT “WR” were used. The compression strengths of ten cylindrical samples of each material were tested. The porosity of each cement was investigated by using micro-computed X-ray tomography. Finite element analysis (FEA) was used to simulate three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The aim of endodontic microsurgery is to preserve teeth that have not responded to the traditional orthograde treatment or retreatment. Various factors can affect the healing of the resected tooth, including the formation of cracks during apicoectomy and root-end preparation, 16 retrograde cavity design, 28 retrograde filling materials, 29 and the homogeneity and roughness of the sectioned surfaces. 19 In addition, certain materials used in root canal obturation may exert biological, 30 mechanical, 28,31 and physicochemical 32 effects on the tooth's canal system, including dentinal tubules and overall structure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim of endodontic microsurgery is to preserve teeth that have not responded to the traditional orthograde treatment or retreatment. Various factors can affect the healing of the resected tooth, including the formation of cracks during apicoectomy and root-end preparation, 16 retrograde cavity design, 28 retrograde filling materials, 29 and the homogeneity and roughness of the sectioned surfaces. 19 In addition, certain materials used in root canal obturation may exert biological, 30 mechanical, 28,31 and physicochemical 32 effects on the tooth's canal system, including dentinal tubules and overall structure.…”
Section: Discussionmentioning
confidence: 99%
“…Various factors can affect the healing of the resected tooth, including the formation of cracks during apicoectomy and root-end preparation, 16 retrograde cavity design, 28 retrograde filling materials, 29 and the homogeneity and roughness of the sectioned surfaces. 19 In addition, certain materials used in root canal obturation may exert biological, 30 mechanical, 28,31 and physicochemical 32 effects on the tooth's canal system, including dentinal tubules and overall structure. BioRoot RCS was used in the present study due to its previously observed bioactivity such as Ca 2þ release, pH changes, and the remineralization process.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, clinical studies should be conducted to confirm these laboratory findings. Furthermore, a single finite element model was used following the protocols of validated finite element studies [40,71]. It is, however, of particular importance to note that patient-specific parameters such as the root canal anatomy could influence the biomechanical behavior of the tooth [72] and should be investigated in future studies using a higher number of finite element models.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies noted that any change or error in the powder liquid ratio during mixing could affect the setting time and physicochemical properties of these materials [17]. Recently, Well Root PT (Vericom, Gangwon-do, Republic of Korea), a novel premixed bioceramic material, was introduced in the dental market and its physicochemical, antibacterial, and mechanical properties were investigated [17,19]. Until now, there has been no clinical study that used this new material in a revascularization procedure.…”
Section: Introductionmentioning
confidence: 99%